Going Separate Ways? School-to-Work Transitions in the United States and Europe - Quintini, Glenda (OECD Social, Employment and Migration Working Papers, 2009)
This paper derives school-to-work transition pathways in the United States and Europe between the late 1990s and the early 2000s. To do so, it uses Optimal Matching, a technique developed to sequence DNA. The key advantage of using this technique is that, rather than focusing on a specific point in time or a single destination, such as employment, inactivity or unemployment, they convey information on all activities undertaken by youth over the transition period, their sequence and their persistence. Strong similarities are found between the United States and Europe. However, pathways in the United States are characterised by significantly more dynamism than in Europe: youth in employment tend to change jobs more frequently while inactive or unemployed youth are more likely to experience several short spells rather than a single long one. School-to-work transition pathways in the United States also involve less time spent in unemployment than in Europe.